A Comparative Study of the Application of Passive Defense Strategies from the Perspective of Urban Design at International Airports: International Airports of Ben-Gurion, Munich and Singapore Changi - Ghanbarpour, Hoda; Kachoee, Mohammad Hassan Ataee; Nezafat, Mahtab (Journal of History Culture and Art Research, 2017)
Billions are spent every year to construct vital infrastructures around the world. On the other hand, we witness terrorist crimes and the killing of innocent people and causing serious physical and psychological damages to them every day in every corner of the world. Unfortunately, today this trend has not been stopped and likely will continue. So, due to the fact that the most important issue in urban design is human and the most important goal is to create safe and stable places for them, it can be concluded that in critical infrastructure such as airports, which are a priority to strategies to deal with terrorist threats, public areas vulnerabilities against terrorist threats have to be investigated to understand the weaknesses of the target infrastructures. So, determining its attractiveness for the invasion, civil defense measures can be taken to reduce vulnerability. In this regard, urban design principles should be applied to reduce the blast effects and to minimize the damage in the public areas of airports. In this study, by implementing an analytical-descriptive methodology, we attempt to identify urban design guidelines resistant to terrorist bombings in public areas of airport environments. The findings of this study show that in achieving terrorist blast-resistant urban design, deployment of strategies in the field of building components, atmosphere, design, and urban landscape will reduce the vulnerability of airports.